Assessment of gaps of knowledge and practices of frontline community workers in Chandragiri Mandal, Chittoor district, Andhra Pradesh: maternal and child health services - Dudala, Shankar Reddy; Ponna, Sathyendra Nath; Upadrasta, Venkata Prasad; Bathina, Hemalatha; Sadasivuni, Renuka; Geddam, J. J. Babu; Kapu, Ashok Kumar Reddy (International Journal Of Community Medicine And Public Health, 2021)
Background: The undernutrition status among the vulnerable groups in rural areas still persists, despite provision of Anganwadi services in villages. Assessment knowledge and practices about maternal and child health services of frontline workers, will identify knowledge and implementation gaps. Objective was to assess the knowledge, attitude and practices of community health workers of maternal and child health services for identifying gaps for designing and implementing intervention. Methods: In this community based prospective, pre and post intervention-based study, Knowledge, Attitude and Practices (KAP) of the community health workers, in 16 villages and 13 Anganwadi centres of Chandragiri Mandal, Chittoor district, Andhra Pradesh about maternal and child health services were collected. The basic infrastructure of the anganwadis and health centres of Auxiliary nurse midwifes were assessed using a prevalidated survey instrument. Descriptive analysis was used. Results: The knowledge of antenatal and postnatal care was least among Anganwadi workers. Awareness regarding need of colostrum feeding was high in AWW compared to ASHA. ANM and AWW had lesser knowledge about duration of the exclusive breast feeding to the infant. Only 57.1% of ANM had sufficient knowledge about protein energy malnutrition consequences. AWW, ASHA did not have knowledge of vitamin A deficiency signs and symptoms although providing massive dose of vitamin A to children. ASHAs did not have awareness about anaemia and the knowledge was below 50% in ANMs. Conclusions: The study emphasizes the need for proper training with interactive sessions to these frontline workers, which will enhance their knowledge and skills for provision of quality services.